(untitled) (Theoretical and Applied Linguistics@ro, 2025)
This study investigates the role of heritage language (HL) literacy in shaping phonological awareness and reading skills among Romanian-Italian bilingual children in Italy. Drawing on data from 81 children aged 8-10 and their families, the research compares the performance of bi-literate bilinguals (exposed to formal literacy instruction in Romanian) with that of mono-literate bilinguals (literate only in Italian) and Italian monolinguals. Children completed tasks measuring phonological awareness and word and pseudoword reading in both Romanian and Italian. Parental attitudes toward HL transmission were also assessed through Likert-scale questionnaires and thematic analysis of open-ended responses. Results showed that bi-literate bilinguals outperformed mono-literate peers on phonological tasks in both languages and on Italian pseudoword reading, highlighting the cognitive benefits of dual literacy. Parental attitudes revealed strong support for oral HL maintenance, but divergent views on the value of written Romanian, often shaped by concerns about cognitive load and perceived utility. The findings underscore the importance of institutional and familial support for biliteracy as a driver of linguistic development in multilingual contexts.